PENGUATAN TOLERANSI DAN DIALOG LINTAS IMAN PADA PERAYAAN IDULFITRI DI DUA KABUPATEN PERBATASAN: TIMOR TENGAH UTARA DAN MALAKA - Maria Olivia Suares; Yanuarius Seran; Yohana Aek Klau; Paulus Pedro Langoday (PASCERE: Jurnal Pengabdian kepada Masyarakat, 2025)
Interfaith Community Service (PkM) represents a concrete form of dialogical learning for students of the Pastoral Institute (Sekolah Tinggi Pastoral/STP) St. Petrus of the Diocese of Atambua. This activity was carried out on 30–31 March 2025 at Jami’ Al-Muhajirin Mosque (Kefamenanu, TTU) and Al-Falah Kletek Mosque (Malaka), coinciding with the celebration of Eid al-Fitr. This article describes the social context, the implementation of the program, and its impact on both students and the local community. The findings indicate that direct encounters through interfaith dialogue, communal work, Eid al-Fitr service, and live-in experiences play a significant role in fostering tolerance and social cohesion. These results align with existing studies on religious moderation and tolerance education in Indonesia.